A Study on φ-Symmetric τ-curvature tensor in N(k)-contact metric manifold - Ingalahalli, G.; Bagewadi, C.S. (Carpathian Mathematical Publications, 2014)
In this paper we study τ-curvature tensor in N(k)-contact metric manifold. We study τ-φ-recurrent,τ-φ-symmetric and globally τ-φ-symmetric N(k)-contact metric manifold.